ANALYZING THE CONSUMER PERCEPTION OF FAST-FOOD IN MANADO (CASE STUDY: KFC and McDonald’s) - Rehiara, Yohanis R. (Universitas Sam Ratulangi, 2013)
In Manado there is a lot of habits with all ages are interested to enjoying their time at the Fast-Food for example, a students, college students and others. With a great atmosphere of people in Manado about the Fast-Food, many fast-food also supported by a live band, a gathering of communities, watching football match together and many activities that is a lot to do. This research aims to examine the consumer perception of KFC and McDonald’s in Manado. This research explored the characteristics of consumers perception contribute to selected Fast Food in Manado (KFC and McDonald’s). With the 100 respondents are contributed and the Correspondence Analysis and Perceptual Mapping method is used in this research. The key findings regarding the physical characteristics showed the top three considerations included: Price, Quality and Value. In this case, people in Manado have a different perception toward Fast Food variant of KFC and McDonald’s. In addition the demographics of age and gender to have more exploration in details about the customer preferred Fast Food. Keywords: consumer perception, perceived price, perceived quality, perceived value.